Tinjauan Analisis Sentimen Terkait COVID-19 - Al Sidqi, Muhammad Affan; Afrizal, Nabil Nur; Rodiansyah, Novan; Cahyana, Rinda (Journal of Digital Literacy and Volunteering, 2025)
The Covid-19 pandemic control policy has created public opinion on social media. The government controls sentiment so that people remain compliant with the policy. Several previous studies have analyzed sentiment with various approaches. This study aims to describe how to analyze sentiment related to the pandemic of earlier studies with a traditional literature review approach through the literature survey stage. The results of the review found various approaches to data collection and sentiment analysis that have been applied by previous studies and their challenges, as well as opportunities for further research.